Constructing a new framework for rural development - Milone, Pierluigi; Ventura, Flaminia; Ye, Jingzhong (Research in rural sociology and development ;, 2015)
This volume seeks to answer modern questions and concerns regarding peasants, their production techniques, and their links to wider society. In the past, peasants and their seemingly simple production models have been criticized for being unable to fully meet the needs of modern society, especially when it comes to world hunger, food quality, and sustainability. However, often neglected is the myriad of new initiatives that alter the way food is produced and marketed. New âpeasant marketsâ are created everywhere and new products and services abound. This volume argues that these initiatives represent âseeds of transitionâ; they are the âsproutsâ out of which new socio-technical modes for organizing production and marketing emerge â âsproutsâ that, taken together, can be summarized as ârural developmentâ. This book critically discusses these new practices and the actors engaged in them. In doing so, it deals with several countries in three different continents (Asia, South America and Europe). It proposes new concepts and approaches for a better understanding of the re-emergence of peasants as indispensable part of modern societies.